Cross-cultural examination of successful entrepreneurial small and medium-sized enterprises - Balhico, A. (2023)
Purpose The purpose of this study is to evaluate the potential variances in strategic entrepreneurial small and medium-sized enterprises (SMEs) across different countries while also exploring the cultural implications that may arise. Design/methodology/approach In this study, a qualitative research approach was used, involving semi-structured interviews conducted with seven technology start-ups from two countries – Portugal and France. Findings The results of this study demonstrate significant differences in opportunity-seeking, performance and long-term orientation behaviors between the technology start-ups in Portugal and France. Practical implications This knowledge can help entrepreneurs and investors make informed decisions when developing strategies, entering new markets or seeking partnerships with start-ups from different countries. Furthermore, policymakers can use these findings to support entrepreneurship initiatives and foster an environment that encourages strategic entrepreneurship practices. Originality/value This study offers a unique perspective by focusing on the firm level of entrepreneurial SMEs and the strategic practices adopted by technology start-ups in Portugal and France. In contrast, prior studies have predominantly centred on analysing individual motivations for entrepreneurship, such as personal traits or attitudes, rather than exploring the actual strategic behaviors and practices of start-ups in various countries. By shifting the emphasis to the firm level, this study provides a more comprehensive understanding of how strategic entrepreneurship practices differ across different cultural contexts. As such, it represents a significant contribution to the existing literature on strategic entrepreneurship.